Testing the 87Sr/86Sr isotopic ratio measured by ICP-MS as a tracer for inter-well investigation in oil reservoirs - Palmieri H.E.L.; dos Santos M.E.; Moreira R.M. (EPJ Web of Conferences, 2013)
The use of the 87Sr/86Sr isotope ratio has been tested as a natural tracer for inter-well tests in oil reservoirs using standard mass-spectrometry equipment. Such an application can have a special interest to offshore oil fields. Strontium is a relatively abundant component of the dissolved solids in seawater and exhibits a rather constant concentration worldwide. It is also present in the formation water in oil reservoirs in a different concentration and with different isotopic signatures. Hence seawater injection procedures in secondary recovery of the oil can disturb the original isotope ratio in a way that may reflect what is happening inside the reservoir. This study is concerned with the breakthrough of the injected water in production wells. The capability of a single collector quadrupole internal coupled plasma mass spectrometer for detecting the small variations in the 87Sr/86Sr ratio is evaluated. The strategy for dealing with isobaric interference is addressed. The isotope ratio approach is compared with the straightforward use of strontium concentration as the tracer.